Optimasi Analytic Hierarchy Process (AHP) dalam Penerimaan Siswa Baru pada Sekolah Menengah Kejuruan menggunakan Algoritme Evolution Strategies - Maya Febrianita; Edy Santoso; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Admission of new students is an activity that is done every school period. One of them is also applied to Vocational High School. Grades from there are referred to as graduates ready to work who have greater potential with equivalent schools. This can certainly cause problems if the level is not maximal. To solve this problem, we apply Analytic Hyrarchy Process (AHP) and Evolution Strategies (ES) algorithm. The ES algorithm will perform the weight optimization of the AHP process. This algorithm has a chromosome length of 6 genes, each gene representing the value of each element of the weight matrix. The Reproduction in this case is only a mutation without recombination. In the evaluation, AHP process determine admission of new student then will be calculated its fitness by using accuracy formula. Selection method uses elitism selection. Based on the results of the research that has been done obtained with the optimal parameter of population size 60, the number offspring is 50 and the number of generations 14 with a fitness value of 0.8869 or with an accuracy of 88.69%. Admission of new student will be shown to users as the final result of the system.